Calretinin: a gene for a novel calcium-binding protein expressed principally in neurons [published erratum appears in J Cell Biol 1990 May;110(5):1845] (The Rockefeller University Press, 1987)
A novel gene of the calmodulin superfamily, encoding a 29-kD neuronal protein here named "calretinin," has been isolated as a cDNA clone from chick retina. The encoded sequence includes four putative calcium- binding sites and a fusion protein binds calcium. The most similar protein known is the 28-kD intestinal calcium-binding protein, calbindin (58% homology). Both genes date from before the divergence of chicks from mammals. The distribution of calretinin and calbindin mRNAs in chick tissues has been mapped using RNA gel blots and in situ hybridization. RNAs from both genes are abundant in the retina and in many areas of the brain, but calretinin RNA is absent from intestine and other nonneural tissues. Calretinin and calbindin are expressed in different sets of neurons throughout the brain. Calretinin RNA is particularly abundant in auditory neurons with precisely timed discharges.